Nonlinear dynamics of a fluid-conveying pipe under the combined action of cross-flow and top-end excitations. (January 2017) - He, Fang; Dai, Huliang; Huang, Zhenhua; Wang, Lin
Highlights: Quasi-static displacement is used to describe the pipe vibration due to the top-end excitation. The combined actions of the internal flows and top-end excitation can significantly increase or decrease the VIV amplitude of the pipe. The sudden transition between quasi-periodic and periodic responses can be observed when the cross-flow speed is in the lock-in region. Abstract: We report a theoretical investigation of an elastic and slender fluid-conveying pipe with a top-end excitation subjected to uniform cross flows. Considering the mean drag force and the time varying vortex-induced lift force which is modeled using a nonlinear van der Pol oscillator, the nonlinear partial differential equations of the motion of coupled fluid-structure system are constructed and simplified to a reduced-order model through the Galerkin-type discretization. By virtue of quasi-static displacement conditions, the characteristics of vortex-induced vibration of the pipe are evaluated for the first two lock-in modes. The results show that the top-end excitation can increase the vibration amplitude of the pipe when the cross-flow speed is out of the lock-in regions. When the cross-flow speed is within the lock-in region, however, the top-end oscillation causes a transition between quasi-periodic and periodic in the responses of the pipe, significantly reducing or increasing the vibration amplitudes depending on the excitation acceleration and frequency. This finding has an important guidance in suppressing vortex-induced vibrations by balancing the internal fluid velocity and the top-end excitation.